Hypoxemia, Bradycardia, and Multiple Laryngoscopy Attempts during Anesthetic Induction in Infants: A Single-center, Retrospective Study. (October 2019) - Gálvez, Jorge A.; Acquah, Samuel; Ahumada, Luis; Cai, Lingyu; Polanski, Marcia; Wu, Lezhou; Simpao, Allan F.; Tan, Jonathan M.; Wasey, Jack; Fiadjoe, John E.
Abstract : Background: The infant airway is particularly vulnerable to trauma from repeated laryngoscopy attempts. Complications associated with elective tracheal intubations in anesthetized infants may be underappreciated. We conducted this study of anesthetized infants to determine the incidence of multiple laryngoscopy attempts during routine tracheal intubation and assess the association of laryngoscopy attempts with hypoxemia and bradycardia. Methods: We conducted a retrospective cross-sectional cohort study of anesthetized infants (age less than or equal to 12 months) who underwent direct laryngoscopy for oral endotracheal intubation between January 24, 2015, and August 1, 2016. We excluded patients with a history of difficult intubation and emergency procedures. Our primary outcome was the incidence of hypoxemia or bradycardia during induction of anesthesia. We evaluated the relationship between laryngoscopy attempts and our primary outcome, adjusting for age, weight, American Society of Anesthesiologists status, staffing model, and encounter location. Results: A total of 1, 341 patients met our inclusion criteria, and 16% (n = 208) had multiple laryngoscopy attempts. The incidence of hypoxemia was 35% (n = 469) and bradycardia was 8.9% (n = 119). Hypoxemia and bradycardia occurred in 3.7% (n = 50) of patients. Multiple laryngoscopy attempts were associated with an increased risk of hypoxemia (adjusted odds ratio: 1.78, 95% CI: 1.30 to 2.43, P < 0.001). There was no association between multiple laryngoscopy attempts and bradycardia (adjusted odds ratio: 1.23, 95% CI: 0.74 to 2.03, P = 0.255). Conclusions: In a quaternary academic center, healthy infants undergoing routine tracheal intubations had a high incidence of multiple laryngoscopy attempts and associated hypoxemia episodes. Abstract : In a quaternary pediatric academic center, 16% of healthy infants undergoing routine tracheal intubations had multiple laryngoscopies. There was also a 35% incidence of hypoxemia, defined as an oxygen saturation measurement less than 90%, during induction of anesthesia. There was evidence for an association between multiple laryngoscopies and hypoxemia.Supplemental Digital Content is available in the text.